Nitrogen-rich graphene hollow microspheres as anode materials for sodium-ion batteries with super-high cycling and rate performance. (April 2018) - Yue, Xiyan; Huang, Ning; Jiang, Zhongqing; Tian, Xiaoning; Wang, Zhongde; Hao, Xiaogang; Jiang, Zhong-Jie
Abstract: Nitrogen-rich graphene hollow microspheres (NGHMs) have been synthesized by simply calcining the core@shell polystyrene@graphene oxide (PS@GO) microspheres in the presence of melamine. These NGHMs are highly active as the anode for sodium ion batteries (SIBs) and can deliver a stable reversible capacity of 253.8 mAh g −1 at 100 mA g −1, which is much higher than that of the conventional nitrogen doped graphene (102.3 mAh g −1 ). Additionally, the NGHMs exhibit excellent rate and cycling performance. A high stable discharge capacity of 77.8 mAh g −1 could be observed when the NGHMs are cycled for 8000 cycles at 10 A g −1 . At 20 A g −1, the NGHMs can still deliver a reversible capacity of 66.7 mAh g −1 . The capacities of the NGHMs are higher than those of most carbonaceous materials reported. These results strongly suggest that the NGHMs are usable as the anode for the SIBs with high-rate performance and super-long life time. The specific hollow structure is found to play an important role in the high performance of the NGHMs. It does not only increase specific surface area of the NGHMs, allowing for more active sites available to the Na + storage, but also allows a ready diffusion of the Na + ions. Graphical abstract: Image 1